2022
DOI: 10.1021/acs.jctc.2c00578
|View full text |Cite
|
Sign up to set email alerts
|

Fast Screening of Minimum Energy Crossing Points with Semiempirical Tight-Binding Methods

Abstract: The investigation of photochemical processes is a highly active field in computational chemistry. One research direction is the automated exploration and identification of minimum energy conical intersection (MECI) geometries. However, due to the immense technical effort required to calculate nonadiabatic potential energy landscapes, the routine application of such computational protocols is severely limited. In this study, we will discuss the prospect of combining adiabatic potential energy surfaces from semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 113 publications
2
21
0
Order By: Relevance
“…An in-depth discussion for these systems can be found in previous work and the citing literature. ,, To summarize the current findings, GFN0-xTB shows virtually identical characteristics as the related self-consistent GFN2-xTB method in the description of GS/OS1 MECPs, which clearly resemble the S 0 / S 1 MECI between adiabatic states. RMSDs at the GFN0-xTB level compared to the reference structures are marginally worse than those with GFN2-xTB, as would be expected for this more approximate non-self-consistent method.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…An in-depth discussion for these systems can be found in previous work and the citing literature. ,, To summarize the current findings, GFN0-xTB shows virtually identical characteristics as the related self-consistent GFN2-xTB method in the description of GS/OS1 MECPs, which clearly resemble the S 0 / S 1 MECI between adiabatic states. RMSDs at the GFN0-xTB level compared to the reference structures are marginally worse than those with GFN2-xTB, as would be expected for this more approximate non-self-consistent method.…”
supporting
confidence: 63%
“…As in previous work, we are pursuing a “derivative coupling vector-free” treatment , that provides MECPs of two (or more) diabatic multidimensional PESs. These points can then serve as approximations to MECIs between adiabatic states that are obtained from multideterminant wave functions .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The preceding ISC from T 1 to the open shell singlet is readily feasible, since for (−)- 3 · 6b , the two states are found to be isoenergetic [−106.9 kJ mol –1 relative to (−)- 2 · ( R )- 1b ] and structurally indistinguishable. The energetically lowest S 0 / S 1 minimum energy conical intersection (MECI) could be identified by a recently developed sampling algorithm (see the Supporting Information for details). Remarkably, among all sampled structures, no precursor geometry could be identified that would correspond to a direct HAT to the prostereogenic carbon atom of radical intermediate 6b .…”
Section: Results and Discussionmentioning
confidence: 99%